2022
DOI: 10.3389/fnbeh.2022.995422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two behavioral tests for tinnitus assessment in mice

Abstract: Animal research focused on chronic tinnitus associated with noise-induced hearing loss can be expensive and time-consuming as a result of the behavioral training required. Although there exist a number of behavioral tests for tinnitus; there have been few formal direct comparisons of these tests. Here, we evaluated animals in two different tinnitus assessment methods. CBA/CaJ mice were trained in an operant conditioning, active avoidance (AA) test, and a reflexive, gap-induced pre-pulse inhibition of acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…These observations indicate that noise induced GPIAS failure in +T mice did not depend on the baseline value of this index before exposure or on its parameters such as postexposure ASR amplitude and BGN intensity. Thus, our results support that the +T and −T groups differ in the presence or intensity of tinnitus and are consistent with the previously described heterogeneous sensitivity of mice to noise-induced tinnitus (Li et al, 2015;Fabrizio-Stover et al, 2022).…”
Section: Differential Sensitivity Of Mice To Tinnitus Inductionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations indicate that noise induced GPIAS failure in +T mice did not depend on the baseline value of this index before exposure or on its parameters such as postexposure ASR amplitude and BGN intensity. Thus, our results support that the +T and −T groups differ in the presence or intensity of tinnitus and are consistent with the previously described heterogeneous sensitivity of mice to noise-induced tinnitus (Li et al, 2015;Fabrizio-Stover et al, 2022).…”
Section: Differential Sensitivity Of Mice To Tinnitus Inductionsupporting
confidence: 92%
“…In humans, differential susceptibility to tinnitus appears to be related to the severity of neuropsychiatric characteristics such as symptoms of depression, anxiety, stress or cognitive impairment (Trevis et al, 2018;Bhatt et al, 2022;Hamed et al, 2023). Research on tinnitus susceptibility using animal models, consistently showing that noise exposure leads to behavioral manifestations of phantom perception in only half of the subjects tested (Li et al, 2015;Mohrle et al, 2019;Fabrizio-Stover et al, 2022), then further suggested cellular and molecular mechanisms of resistance to tinnitus induction. These include plasticity of glutamatergic synapses in the cochlear nucleus, restoration of KCNQ2/3 potassium channel activity in principal dorsal cochlear nucleus neurons, potentiation of auditory brainstem responses along with expression of the immediateearly Arc/Arg3.1 gene, and increased GABAergic inhibition in the auditory cortex (Li et al, 2013;Ruttiger et al, 2013;Li et al, 2015;Heeringa et al, 2018;Miyakawa et al, 2019;Deng et al, 2020;Masri et al, 2021; also see Shore et al, 2016;Shore and Wu, 2019;Henton and Tzounopoulos, 2021 for reviews).…”
Section: Introductionmentioning
confidence: 99%